2013
DOI: 10.1016/j.jaad.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus in patients treated with targeted cancer therapies: Systematic review and meta-analysis

Abstract: Background Pruritus has been anecdotally described in association with targeted cancer therapies. The risk of pruritus has not been systematically ascertained. Objective A systematic review and meta-analysis of the literature was conducted for axitinib, cetuximab, dasatinib, erlotinib, everolimus, gefitinib, imatinib, ipilimumab, lapatinib, nilotinib, panitumumab, pazopanib, rituximab, sorafenib, temsirolimus, tositumomab, vandetanib, and vemurafenib. Methods Databases from PubMed, Web of Science (01/1998–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 153 publications
(60 reference statements)
3
52
0
2
Order By: Relevance
“…Pruritus associated with targeted therapies has been shown to be a source of chemotherapy dose reduction and interruption, 12 but the effect of xerosis had not been assessed. In our metaanalysis of published trials, we found that patients receiving targeted therapies were at a significantly increased risk of developing xerosis during treatment (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pruritus associated with targeted therapies has been shown to be a source of chemotherapy dose reduction and interruption, 12 but the effect of xerosis had not been assessed. In our metaanalysis of published trials, we found that patients receiving targeted therapies were at a significantly increased risk of developing xerosis during treatment (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…161 Untreated dry skin is often the precursor of pruritus and excoriated skin, perpetuating breakdown of the skin barrier. 12 Timely identification and treatment of xerosis may halt the evolution into more serious skin complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of 18 TCT drugs found 17.4% incidence of all-grade pruritus 108 . Alopecia can occur with BRAF (vemurafenib, dabrafenib) 109 and VEGFR inhibitors (sorafenib) 110 , albeit at significantly lower frequency than with conventional chemotherapy.…”
Section: Dermatologic Toxicitiesmentioning
confidence: 99%
“…2015 Informa UK Ltd www.cmrojournal.com Risk of mucocutaneous toxicities associated with lapatinib Abdel-Rahman & Fouad 983 [95% CI 1.76-4.77; p50.001]) with targeted cancer therapies with variation among different drugs (p50.001)44 .…”
mentioning
confidence: 99%